The Concept of Heart-Oriented Rhotrix Multiplication (Global Journal of Science Frontier Research, 2011)
This paper introduces the concept of heart-oriented rhotrix multiplication. A generalized representation of n-dimensional heart-oriented rhotrices viewed from the direction of single array indices and double array row-wise indices is presented. We provided a simplified compact mathematical expression for the two multiplication process presented in the paper. The given methods were implemented based on the sequential algorithm developed.
Keywords: Heart-oriented rhotrix multiplication; Row-wise rhotrix multiplication; Algorithms